Ingestion of low‐dose ibuprofen following resistance exercise in postmenopausal women. Issue 1 (10th July 2012) - Candow, Darren G.; Chilibeck, Philip D.; Weisgarber, Krissy; Vogt, Emelie; Baxter-Jones, Adam D. G.
Abstract : Background: Postmenopausal women typically experience accelerated muscle loss which has a negative effect on strength. The maximum daily recommended dosage of ibuprofen (1, 200 mg) following resistance exercise has been shown to increase muscle hypertrophy and strength in older adults. This study aimed to determine the effects of low‐dose ibuprofen (400 mg) immediately following resistance exercise sessions on muscle mass and strength in postmenopausal women. Methods: Participants were randomized to ingest ibuprofen (IBU: n  = 15, 57.8 ± 5.1 years, 75.9 ± 9.0 kg, 165.9 ± 6.2 cm, BMI = 28 ± 4 kg/m 2 ) or placebo (PLA: n  = 13, 56.5 ± 4.4 years, 73.0 ± 10.4 kg, 163.1 ± 5.9 cm, BMI = 26 ± 9 kg/m 2 ) immediately following resistance exercise (11 whole‐body exercises), which was performed 3 days/week, on nonconsecutive days, for 9 weeks. Prior to and following training, measures were taken for lean tissue mass (dual‐energy X‐ray absorptiometry), muscle size of the elbow and knee flexors and extensors and ankle dorsiflexors and plantar flexors (ultrasound), and strength (one‐repetition maximum leg press and chest press). Results: Over the 9 weeks of training, there were significant changes ( p  < 0.05) in lean tissue mass (IBU, −1.1 ± 1.0 kg; PLA, −0.7 ± 1.4 kg), muscle size of the knee extensors (IBU, 0.3 ± 0.6 cm; PLA, 0.2 ± 0.7 cm), ankle dorsiflexors (IBU, 0.5 ± 0.8 cm; PLA, 0.1 ± 0.5 cm), and ankle plantar flexors (IBU, 0.3 ± 0.9 cm; PLA, 0.5 ± 0.9 cm), leg press strength (IBU, 20.6 ± 18.0 kg; PLA, 20.0 ± 20.0 kg), and chest press strength (IBU, 5.1 ± 9.5 kg; PLA, 8.1 ± 7.6 kg), with no differences between groups. Conclusion: Low‐dose ibuprofen following resistance exercise has no greater effect on muscle mass or strength over exercise alone in postmenopausal women.